Detection of Sabin Poliovirus Serotypes among Vaccinated Iraqi Children with AFP Syndrom - Al-Garawi, Razaq H.; Alarajy, Kadhim H.; Z., Ayaid Kh. (Iraqi Journal of Science, 2019)
Poliomyelitis is a viral disease caused by an enterovirus known as poliovirus and is well known for its role in causing paralysis in children, the virus is only infectious in humans and does pass into the central nervous system and cause various degrees of paralysis, poliovirus passes newcomer disabuse of suppliant to alms-man thumb the fecal-oral route infected persons still shed the virus in their stool allowing the virus to infect others. The main aim of this study was isolating and differentiation of poliovirus strains (Sabin virus) from the stool samples of children received polio vaccine TOPV and suffering from acute flaccid paralysis. In this study use the cell culture system as the gold-standard method for Culture and isolation of Sabin polioviruses newcomer disabuse of the clinical moderate samples of sharp-witted flaccid paralysis AFP cases. Total of two hundred and fifty (250) stool test was taken from vaccinated children with TOPV who suffering from acute paralysis in Iraq.The samples were collected during the period of the study from (March to November in the year 2017) Were transferred under cold situation the children were stratified according to provinces .Stool test taken within 48 hours were each patient before the fourteenth days after the onset of AFP . The study that 35 (14%) samples were positive for Sabin for poliowere isolated from AFP cases. Showed CPE effect on L20B cells only all the samples were from patient vaccinated with the type of OPV in varying number of orally TOPV dose. The current study which was done in different Iraqi provinces shows that (Sabin for polio of type 3) were isolated from AFP cases had the highest prevalence affecting 18 cases (51. 42 %) out of 35 Sabin of polioviruses AFP. The present study showed that the maximum frequency of (Sabin for polioviruses typo 3) virus isolate was reported in Baghdad 7 ( 38.8%) and both provinces Anbar and Salahdeen shows 3 (16.6%) followed by Wasit and Dyiala 2 case (11.11%), then Duhok 1 case (5.5%). Ten 10 cases (28.57%) of the Sabin AFP polio were mixing isolated (Sabin of polioviruses typo 3 with type 1) these positive cases found in Anbar province in high prevalence 4 cases (40%) followed by Baghdad, Erbil 2 case (20 %) for each then , Duhok and Tamim 1 case ( 10 %) . Seven 7 (20 %) stool samples were positive for Sabin for polio type 1 serotype were isolated from AFP cases the large number of the diagnosis was obtained from a patient in the Baghdad isolate 3 cases (42.85 %) ) followed by Sulymania 2positive cases (28.57 %) then Qadysia and Basrah 1 case (14.28% .